Mengupayakan Pendampingan Pastoral Yang Kontinuitas Terhadap Generasi Z Yang Mengalami Psikosomatis - Meisiela Angel Laoh; Maria E. Tulangouw (PT. Giat Konseling Nusantara, 2026)
Generation Z is a generation that grew up in the fast-paced and competitive digital era, making them vulnerable to psychological pressure that leads to psychosomatic disorders. Psychosomatic symptoms experienced by generation Z are caused by inner conflict, social pressure and identity crisis. Continuous pastoral accompaniment is needed to provide spiritual and emotional attention, as well as help generation Z overcome this challenge. This article criticizes the lack of a pastoral approach that is contextual to the realities experienced by Generation Z and seeks continuous and holistic accompaniment. By integrating theology and psychological understanding, this accompaniment is carried out as a recovery strategy in dealing with psychosomatic problems in generation Z as a whole.